Comparison of intravenous sodium bicarbonate and sodium chloride combination versus intravenous sodium chloride hydration alone in reducing amphotericin B nephrotoxicity: a randomized clinical trial - Iman Karimzadeh; Asma Sepehr-Sobhani; Mohammad Javad Khoshnoud; Mohammad Mahdi Sagheb; Reza Vejdani; Atefeh Jalali; Motahareh Mahi-Birjand (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: The most important adverse reaction of amphotericin B (AmB) is nephrotoxicity. The aim of this study was to assess the potential effectiveness of intravenous saline + sodium bicarbonate versus intravenous sodium chloride hydration in preventing or attenuating AmB nephrotoxicity. Experimental approach: A randomized, non-placebo-controlled, single-blinded clinical trial was conducted in two adult hematology-oncology wards of Namazi hospital. Eligible patients were randomly assigned into either the normal saline or normal saline + sodium bicarbonate groups by the ratio of 1:2. In the normal saline group, 1000 mL of sodium chloride 0.9% (154 meq sodium) was given intravenously as two equal 500 mL volumes before and during the infusion of AmB. Patients in the saline + sodium bicarbonate group received 500 mL sodium chloride 0.9% (72 meq sodium) before and 500 mL isotonic sodium bicarbonate (72 meq sodium) intravenously during AmB infusion. Findings/Results: The rate of AmB nephrotoxicity was comparable between normal saline and sodium bicarbonate groups (54.2% and 41.6%, respectively; P = 0.3). This difference did not reach the level of statistical significance after considering AmB dose and duration of the treatment. The frequency of hypokalemia and hypomagnesemia did not differ significantly between the two groups even after adjusting the results according to AmB dose and treatment duration. Conclusion and implications: The results of the current preliminary clinical trial suggested that the combination of sodium bicarbonate and normal saline compared to normal saline alone appears to have no superiority in preventing or attenuating different studied aspects of AmB nephrotoxicity in patients with hematological malignancies.